2001
DOI: 10.1002/chir.10032
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective degradation of metalaxyl and metalaxyl‐M in soil and sunflower plants

Abstract: A high proportion of agrochemicals are chiral compounds. Since stereoisomers often show different biological and physiological properties, the biological and metabolic responses to these compounds and their fate in the environment are expected to be different. In this work we investigate a possible stereo and/or enantioselective degradation in soil and plants (sunflower) of the fungicide Metalaxyl (rac-Metalaxyl) and the new compound Metalaxyl-M ((-)-(R)-Metalaxyl) and propose procedures for extraction, cleanu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 14 publications
0
63
1
Order By: Relevance
“…Nevertheless, it should be noted that previous works have indicated that metalaxyl enantiomers are configurationally stable in soil, with no interconversion of R to S-enantiomers, and viceversa [31,41]. Furthermore, enantiomerization would not explain the greater total (R+S) sorption of metalaxyl from initial solutions enriched with R enantiomer (Fig.…”
Section: Sorption Of Metalaxyl On Soil From Racemic and Non-racemic Imentioning
confidence: 79%
“…Nevertheless, it should be noted that previous works have indicated that metalaxyl enantiomers are configurationally stable in soil, with no interconversion of R to S-enantiomers, and viceversa [31,41]. Furthermore, enantiomerization would not explain the greater total (R+S) sorption of metalaxyl from initial solutions enriched with R enantiomer (Fig.…”
Section: Sorption Of Metalaxyl On Soil From Racemic and Non-racemic Imentioning
confidence: 79%
“…The (R)<(S) enantioselectivity in metabolism of aryloxyalkanoic acid herbicides was observed in some plant species including green algae, and similarly in soil metabolism, but with no enantiomerization. 82,[112][113][114][115] Similar enantioselectivity was observed for metalaxyl (10) 89,116) and benalaxyl (11), 91) with no enantiomerization of the former herbicide reported. The simple comparison of soil and plant metabolism may suggest less contribution of enzyme-mediated enantiomerization of these pesticides in plants.…”
Section: Plant Metabolismmentioning
confidence: 68%
“…3 (4)]. 86) The opposite enantioselectivity of degradation [(R)>(S)] was reported for acetoanilide herbicide metalaxyl (10) [88][89][90]93) and benalaxyl (11), 91,92) while the same enantioselectivity as aryloxyalkanoic acids was observed for the acid metabolite of metalaxyl (10).…”
Section: Microbial Degradation In Soilmentioning
confidence: 94%
“…Metalaxyl-M [the (-)-(R)-enantiomer of methyl-N-(2-methoxyacetyl)-N-(2,6-xylyl)-DL-alaninate] is the most widely known member of the phenylamide class of fungicides. It destroys the fungi by interacting with the fungal RNA polymerase I-template complex, thus inhibiting the incorporation of ribonucleotides in nascent RNA [1]. On the other hand, fosthiazate is an efficient nematicide and a member of the organophosphate class of pesticides (OPs).…”
Section: Introductionmentioning
confidence: 99%